1984
DOI: 10.1159/000199103
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline-Induced Fulminant Hepatitis

Abstract: The authors report the case of a patient who received amitriptyline on 2 occasions. On both occasions, she had fever and jaundice. On the second episode, hepatitis was severe with hepatic encephalopathy, ascites, increased prothrombin time, and massive hepatic necrosis. After interruption of the drug administration, the patient made a slow but complete recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Impipramine, amitriptyline, and chlorimipramine seem to be more often related to liver toxicity (59). Possible cross-toxicity between tricyclic antidepressants and phenothiazine is possible (60).…”
Section: Resultsmentioning
confidence: 99%
“…Impipramine, amitriptyline, and chlorimipramine seem to be more often related to liver toxicity (59). Possible cross-toxicity between tricyclic antidepressants and phenothiazine is possible (60).…”
Section: Resultsmentioning
confidence: 99%
“…A case of disturbed hepatic architecture due to massive liver necrosis with portal areas containing lymphocytes and a significant amount of eosinophils was described in an imipramine-treated patient (Ilan et al 1996 ). Amitriptyline-induced hepatitis with infiltration of mononuclear cells, neutrophils, and eosinophils (Larrey et al 1988 ), as well as with massive necrosis and an intense inflammatory reaction (Danan et al 1984 ) were also demonstrated. Recently, another acute hepatitis case due to amitriptyline was reported (Chen et al 2019 ).…”
Section: Major Pathophysiological Pathways In Dilimentioning
confidence: 99%
“…Experience with the newer antidepressant agents in patients with hepatic disease is limited. There have been case reports of hepatic toxicity with fluoxetine, venlafaxine, nefazodone, paroxetine, sertraline, moclobemide, imipramine, nortriptyline, amitriptyline, maprotiline, desipramine, phenelzine and trazodone [79][80][81][82][83][84][85][86][87][88][89][90][91]. Clearance of sertraline, paroxetine, fluvoxamine, fluoxetine, and nefazodone was found to be reduced with significant prolongation in elimination halflife in hepatic impaired patients [92][93][94][95][96].…”
Section: Antidepressantsmentioning
confidence: 99%